In situ imaging of quantum dot-AZD4547 conjugates for tracking the dynamic behavior of fibroblast growth factor receptor 3 - Hwang G (Dove Medical Press, 2017)
Gyoyeon Hwang,1,2,* Hyeonhye Kim,1,* Hojong Yoon,1 Chiman Song,1 Dong-Kwon Lim,3 Taebo Sim,1,3 Jiyeon Lee1,2 1Chemical Kinomics Research Center, Materials and Life Science Research Division, Korea Institute of Science and Technology, Seoul, 2Bio-Med, Korea University of Science and Technology, Daejeon, 3KU-KIST Graduate School of Converging Science and Technology, Korea University, Seoul, Republic of Korea *These authors contributed equally to this work Abstract: Fibroblast growth factor receptors (FGFRs) play an important role in determining cell proliferation, differentiation, migration, and survival. Although a variety of small-molecule FGFR inhibitors have been developed for cancer therapeutics, the interaction between FGFRs and FGFR inhibitors has not been well characterized. The FGFR–inhibitor interaction can be characterized using a new imaging probe that has strong, stable signal properties for in situ cellular imaging of the interaction without quenching. We developed a kinase–inhibitor-modified quantum dot (QD) probe to investigate the interaction between FGFR and potential inhibitors. Especially, turbo-green fluorescent protein-FGFR3s were overexpressed in HeLa cells to investigate the colocalization of FGFR3 and AZD4547 using the QD-AZD4547 probe. The result indicates that this probe is useful for investigating the binding behaviors of FGFR3 with the FGFR inhibitor. Thus, this new inhibitor-modified QD probe is a promising tool for understanding the interaction between FGFR and inhibitors and for creating future high-content, cell-based drug screening strategies. Keywords: quantum dot, fibroblast growth factor 3, AZD4547, kinase–inhibitor, in situ imaging